2019
DOI: 10.3389/fped.2019.00180
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol 0.2% Eye Micro-Drops for Retinopathy of Prematurity: A Prospective Phase IIB Study

Abstract: Background: Oral propranolol reduces retinopathy of prematurity (ROP) progression, although not safely. Propranolol 0.1% eye micro-drops administered to newborns with stage 2 ROP are well-tolerated, but not sufficiently effective. Methods: A multi-center open-label trial was conducted to assess the safety and efficacy of propranolol 0.2% eye micro-drops in newborns with stage 1 ROP. The progression of the disease was evaluated with serial ophthalmologic examinations. Hemodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 35 publications
(53 reference statements)
0
38
0
Order By: Relevance
“…However, studies in preterm infants have raised concern for both efficacy and safety. Although oral propranolol showed promise in halting ROP progression, there was an increase in adverse life-threatening side-effects in pilot clinical trials [100], and a recent multi-center phase IIB study using 0.2% propranolol in newborns with stage 1 ROP reported that despite overall favorable treatment results, early treatment resulted in worse ROP disease, suggesting that a β-adrenoreceptor blockade is only useful during the proliferative phase [101]. These findings may harmonize the disparate data with regard to efficacy of propranolol for ROP treatment, but nevertheless raise concern for preventive β-adrenoreceptor inhibition in ROP.…”
Section: Beta Blockersmentioning
confidence: 99%
“…However, studies in preterm infants have raised concern for both efficacy and safety. Although oral propranolol showed promise in halting ROP progression, there was an increase in adverse life-threatening side-effects in pilot clinical trials [100], and a recent multi-center phase IIB study using 0.2% propranolol in newborns with stage 1 ROP reported that despite overall favorable treatment results, early treatment resulted in worse ROP disease, suggesting that a β-adrenoreceptor blockade is only useful during the proliferative phase [101]. These findings may harmonize the disparate data with regard to efficacy of propranolol for ROP treatment, but nevertheless raise concern for preventive β-adrenoreceptor inhibition in ROP.…”
Section: Beta Blockersmentioning
confidence: 99%
“…During the last 6-year, five studies 48, [57][58][59][60] have been published with the use of oral propranolol as a treatment or prophylaxis and two studies using propranolol drops of ROP. 61,62 One of the first publications by Filippi et al 57 in 2013 evaluated the safety and effectiveness of oral propranolol in 52 preterm infants with ROP. This study showed a tendency to a decrease of the progression to stage 4 ROP and a decrease in the need for laser treatment and or bevacizumab.…”
Section: β-Adrenergic Blockers: Propranololmentioning
confidence: 99%
“…61 The same group of researchers conducted a second study, increasing the concentration of propranolol eye microdrops to 0.2%. 62 They studied 98 VLBW infants with ROP stage 1 and compared it with a historical control group. They demonstrated that progression of ROP to stage 2 or 3 plus was significantly lower in the group treated with eye microdrops of propranolol versus the historical control group.…”
Section: β-Adrenergic Blockers: Propranololmentioning
confidence: 99%
See 1 more Smart Citation
“…A first clinical trial performed in newborns with stage 2 ROP demonstrated that propranolol 0.1% eye micro-drops were well-tolerated, but not sufficiently effective (28). On the contrary, a second clinical trial demonstrated that propranolol eye micro-drops administered a higher concentration (0.2%) and started at an earlier stage of the disease (stage 1 ROP) reduced ROP progression and showed an excellent safety profile (29).…”
Section: Introductionmentioning
confidence: 99%